Deputy Principals’ Self-Efficacy in Dealing with Bullying in Malaysian Secondary Schools - Lee, J.C.; Abdul Rahman, N.A.; Narawi, M.S. (Penerbit Akademia Baru, 2016)
With the increased use of the internet and social media, students are now being bullied in all locations, at all times. Bullying among students seems unstoppable. As second in command in the structure of secondary schools, the Deputy Principals have to face and deal with this problem. As Deputy Principals remain to be one of the least understood roles among schools of contemporary education systems, scant attention was paid to their self-efficacy regarding dealing with bullying. The purpose of this study is to identify the levels of secondary schools Deputy Principals’ self-efficacy (Behavioral, Cognitive, and Emotional) in terms of dealing with bullying among students. 960 inservice Deputy Principals, 3748 students, and 798 parents from 240 secondary schools throughout Malaysia were involved in this study. Based on the finding of this study, Behavioral Self-Efficacy has the highest overall mean. However, the level of agreement towards Deputy Principals’ Behavioral Efficacy in dealing with bullying, from both students and parents involved in this study is considered quite low. With better training opportunities and ongoing professional development for Deputy Principals in order to enhance their behavioral, cognitive, and emotional efficacy in dealing with bullying, hopefully will help to ease the problem of bullying among students in schools.